Effect of Selected Luting Agents on the Retention of CAD/CAM Zirconia Crowns under Cyclic Environmental Pressure - Leyla Sadighpour; Farideh Geramipanah; Akbar Fazel; Mahdi Allahdadi; Mohamad Javad KharaziFard (Tehran University of Medical Sciences, 2018)
Objectives: The aim of this study was to evaluate the retention strength of zirconia crowns luted with two types of resin cement under environmental pressure changes. Materials and Methods: Thirty zirconia crowns were fabricated by using computer-aided design/computer-aided manufacturing (CAD/CAM) system and were cemented by Panavia F2.0 (PAN), hand-mixed RelyX Unicem (UNH), or auto-mix RelyX Unicem Aplicap (UNA) cements on the corresponding extracted human molars. The samples were randomly divided into three groups according to the cement type. After 3000 thermal cycles, the cemented crowns were subjected to 24 pressure cycles (0 to 5 atmospheres). The retention force (N) of the specimens was measured in a universal testing machine. To normalize the retentive force, the recorded force was divided by the surface area of each tooth for measuring the retentive strength (MPa). The mean retention strengths (and forces) of the groups were compared by using one-way analysis of variance (ANOVA) and Tukey's honest significant difference (HSD) test (α=0.05). The failure modes were also examined by using a stereomicroscope. Results: The retention values related to the evaluated resin cements were significantly different; the UNA group showed the highest retention strength (6.45±0.35 MPa) followed by the UNH (4.99±0.47 MPa) and PAN (4.45±0.39 MPa, P<0.001) groups. The adhesive failure mode was predominant in all the groups. Conclusions: The choice of resin cements and their mixing methods, which lead to differences in porosity, may affect the retention strength of zirconia crowns.